Research of the International Food Policy Research Institute in Uganda: Bibliography of internet-accessible research documents produced since 1998 - International Food Policy Research Institute (International Food Policy Research Institute, 2010)
The International Food Policy Research Institute has been undertaking policy research and capacity strengthening activities in Uganda since about 1998. A broad range of research reports, discussion papers, project reports, and other documents have been published as a component of these activities. This bibliography provides citations and web-links for all research-related publications from the work of IFPRI in Uganda that was undertaken by IFPRI researchers or their research partners and that have been published primarily on the websites of IFPRI (http://www.ifpri.org) and of the SCRIP project (http://www.foodnet.cgiar.org/scrip).